(untitled) (Indian Journal of Arid Horticulture, 2013)
A field experiment was conducted in a Typic Ustochrept soil of Varanasi region (83 0’ Elongitudes and 25 10’ N latitude) with Arkel, Azad P and Azad P varieties of pea under treatment combination of low cost organic inputs plus 1 3 biofertilizers and compared to standard packages of practices. The total biomass, vegetable pea and grain yield of Azad P1 was significantly higher compared to Arkel and Azad P3. The supplementation of sulphur nutrient through pressmud significantly enhanced the yield attributes in all the three tested varieties. Application of Azotobacter alone or in combination with Rhizobium significantly influences the quantitative and qualitative traits in pea. The dual inoculation of Rhizobium / Azotobacter @ 200 g/10 kg seeds and PSB plus soil application of pressmud @ 5t/ha significantly enhanced the yield and quality traits of vegetable and grain pea.